Overcoming Thuggishness in Society in the Context of Providing a Sense of Security (Study in DKI Jakarta Province) - Juniawan Mandala Putra; Vivi Novribe; Menorizah (Jurnal Pengabdian Pancasila (JPP), 2023)
Lately, the number of thuggery in big city areas has become increasingly rampant, both in terms of security guarding and in terms of asking forcibly on behalf of certain persons, this is felt both in the community and in the work environment which often makes people very uncomfortable in the situation. This is caused by the weak security provided by the local government in anticipating the occurrence of thuggery in the social environment, unlike other countries that have implemented a system that prohibits thuggery or illegal extortion that is rampant in social life. In this discussion, the researcher uses a literature review with a descriptive approach and secondary data obtained from DKI Jakarta BPS (Central Bureau of Statistics) and direct interviews with the public. The conclusion is that all kinds of permanent aspects carried out by individuals or groups are illegal and can be criminalized for disturbing public order, this has an Puimpact on all kinds of aspects of society, so from community law enforcement, namely the Satpol PP and the Police and the active community to report if anyone tries to disturb the order.